Kajian Manajemen Pelayanan: Tinjauan Kritis Terhadap Kompleksitas Layanan Akta Kelahiran Untuk Meningkatkan Kualitas Layanan Di Kota Surabaya - Putri, Aurelia Patricia; Fanida, Eva Hany (Publika, 2024)
The Surabaya City Dispendukcapil noted that there were tens of thousands of residents who were late in reporting the birth of their babies, which caused the process of issuing birth certificates to be hampered. In addition, there are still many people who have received poor services. This research aims to describe the Service Management Study: A Critical Review of the Complexity of Birth Certificate Services to Improve Service Quality in Surabaya City. This research focuses on the theory of improving service quality by Septiandin (2020), namely Self esteem (self-esteem / self-quality), Exceed expectation (meeting expectations), Recovery (improvement), Vision (foresight), Improve (improvement), Care (attention), Empower (empowerment). This research uses a descriptive method with a qualitative approach. With data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that the quality of birth certificate services is quite good, but there are still many complex problems such as human error, lack of maximum utilization of technology, lack of training for employees, lack of budget, these problems cause deed services to be less than optimal. The results of this study resulted in several recommendations, namely increasing a friendly attitude in providing services, providing socialization and training for employees, maintaining existing facilities and infrastructure and completing facilities that are still lacking, utilizing and synchronizing technology as much as possible, creating a conducive environment and providing a sense of comfort in services for the community so that birth certificate services run well.